1H NMR-based water-soluble lower molecule characterization and fatty acid composition of Chinese native chickens and commercial broiler. (February 2021) - Xiao, Zhichao; Zhang, Wangang; Yang, Hongtao; Yan, Ziyu; Ge, Changrong; Liao, Guozhou; Su, Huawei
Graphical abstract: Highlights: 57 metabolites found from Chinese native chickens and Cobb chicken meat. 54 metabolites found from Chinese native chickens and Cobb chicken soup. Lactate, anserine, creatine, and IMP were distinguished between the samples. The concentration of flavor compounds was highest in Chinese native chickens. Abstract: The aim of this study was to compare the water-soluble low molecular weight (WLMW) compounds and fatty acids (FAs) in raw meat and chicken soup between the two Chinese native chickens (Wuding chicken and Yanjin silky fowl chicken) and one typical commercial broiler (Cobb chicken). The WLMW compounds of chicken meat was studied using 1 H nuclear magnetic resonance spectroscopy ( 1 H NMR) and the FAs were identified and quantified using gas chromatography-mass spectrometry (GC–MS). Compared with typical commercial broiler, the main flavor substances (WLMW compounds and FAs) content were significantly higher in the breast and leg meat of the two Chinese native chickens ( P  < 0.05). Instead, the content of main flavor compounds was significantly higher in chicken soup of typical commercial broiler ( P  < 0.05). These results contribute to a further understanding the distinction of the flavor compounds between the typical commercial broiler and Chinese native chickens, which could be used to help assess the meat quality of different local broilers.